Development of an android-based math equation editor. (March 2020) - Nuraeni, Z; Rosyid, A; Mahpudin, A; Suparman,; Andriyani,
Abstract: The long-term goal of this research is to develop Android-based learning as an alternative to mathematics learning. Meanwhile, the specific objective to be achieved in this research is to examine the effect of Mathematics learning media in the form of an Android-based Math Equation Editor on student achievement in high school. This research is a Research and Development (R&D) research. There are 8 stages in this study, namely (1) Potential and problems, (2) Data collection, (3) Product design, (4) Design validation, (5) Design revision, (6) Product testing, (7) Design revision, and (8) Trial usage. The conclusions obtained from the development of the Android-based Mathematical Equation Editor as an exponential learning media are valid, practical and effective. The conclusions of this study are: (1) Android-based Math Equation Editor Products are valid, practical and effective. Its validity can be seen from the results of the validator assessment analysis of the Mathematics learning media in the form of an Android-based Math Equation Editor obtained by Pearson correlation of 0.322; (2) Its practicality is seen from the results of user assessment analysis through limited trials of Mathematics Equation Editor-shaped learning media in the form of Android which shows an average score of 3.958 with practical criteria; (3) Its effectiveness is seen from the results of the analysis of student assessments through field trials of Mathematics Equation Editor-shaped learning media based on Android can improve student mathematics learning achievement in Mathematic.